Compositional Heterogeneity of Impact Melt Rocks at the Haughton Impact Structure, Canada: Implications for Planetary Processes and Remote Sensing. Issue 10 (2nd October 2020) - Greenberger, Rebecca N.; Ehlmann, Bethany L.; Osinski, Gordon R.; Tornabene, Livio L.; Green, Robert O.
Abstract: Connecting the surface expression of impact crater‐related lithologies to planetary or regional subsurface compositions requires an understanding of material transport during crater formation. Here, we use imaging spectroscopy of six clast‐rich impact melt rock outcrops within the well‐preserved 23.5‐Ma, 23‐km diameter Haughton impact structure, Canada, to determine melt rock composition and spatial heterogeneity. We compare results from outcrop to outcrop, using clasts, groundmass, and integrated clast‐groundmass compositions as tracers of transport during crater‐fill melt rock formation and cooling. Supporting laboratory imaging spectroscopy analyses of 91 melt‐bearing breccia and clast samples and microscopic X‐ray fluorescence elemental mapping of cut samples paired with spectroscopy of identical surfaces validate outcrop‐scale lithological determinations. Results show different clast‐rich impact melt rock compositions at three sites kilometers apart and an inverse correlation between silica‐rich (sandstone, gneiss, and phyllosilicate‐rich shales) and gypsum‐rich rocks that suggests differences in source depth with location. In the target stratigraphy, gypsum is primarily sourced from 1‐km depth, while gneiss is from >1.8‐km depth, sandstone from >1.3 km, and shales from 1.6–1.7 km. Observed heterogeneities likely result from different excavation depths coupled with rapid quenching of the melt due to high content of cool clasts. Results provide quantitative constraints for numerical models of impact structure formation and give new details on melt rock heterogeneity important in interpreting mission data and planning sample return of impactites, particularly for bodies with impacts into sedimentary and volatile‐bearing targets, e.g., Mars and Ceres. Plain Language Summary: When extraterrestrial asteroids/comets over a certain size strike Earth's surface or other Solar System bodies, they form craters, and their energy brings buried rocks to the surface where we can study them. This process melts some rocks, which mix with unmelted rock and solidify to form a new rock type, impact melt rock. A key question is how much the melt rock's composition changes around the crater, which tells us if and how impact melt rocks preserve the nature of buried materials, which are otherwise unobservable. We used a portable imaging spectrometer instrument. Each pixel in the resulting image records visible and infrared light reflected off the rock. The way the rock absorbs light indicates the minerals present and how much of each is in the melt rock. We studied a crater in Canada by measuring large field outcrops and small lab samples. Across all spatial scales, we find large differences in impact melt rock composition with location in the crater, recording rocks excavated from different depths. These results improve our understanding of how craters form, provide percentage differences in composition that computational models of crater formation must reproduce, and help interpret similar rocks observed on Mars, Ceres, and elsewhere. Key Points: Compositions of outcrops of impact melt rock at the Haughton impact structure were determined quantitatively using imaging spectroscopy Impact melt rock in this sedimentary target is incompletely mixed and heterogeneous Clasts and groundmass in the melt rock are sourced from different depths in the target stratigraphy depending on location in the structure